2008
DOI: 10.1519/jsc.0b013e31818218e1
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Stretching Exercises on Muscular Endurance

Abstract: This study aims to evaluate the acute effects of different stretching exercises on muscular endurance in men, in terms of the number of sets, set duration, and type of stretching. Two experiments were conducted; in the first one (E1), the subjects (n = 19) were evaluated to test the effect on the number of sets, and, in the second one (E2), the subjects (n = 15) were tested for the effect of set duration and type of stretching. After a warm-up of 10-15 repetitions of a bench press (BP) with submaximal effort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
1
31

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 17 publications
0
41
1
31
Order By: Relevance
“…According to Sharman et al [26], PNF stretching may elicit autogenic inhibition and a reduction in excitability of contracting or stretched muscles. Franco et al [20] reported a reduction in muscle endurance (maximum repetitions performed at 85% of 1-RM) during a BP exercise following a low dose of PNF stretching (one set of 20 seconds), consisting of a single stretch for the PM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sharman et al [26], PNF stretching may elicit autogenic inhibition and a reduction in excitability of contracting or stretched muscles. Franco et al [20] reported a reduction in muscle endurance (maximum repetitions performed at 85% of 1-RM) during a BP exercise following a low dose of PNF stretching (one set of 20 seconds), consisting of a single stretch for the PM.…”
Section: Discussionmentioning
confidence: 99%
“…The static and PNF stretches applied to the PM muscle were consistent with the protocol previously conducted by Franco et al [20]. Subjects maintained a standing position, preserving the physiological curvature of the spine; the researcher then instituted a passive stretch for the PM via horizontal abduction of the shoulder joints with the elbow joints fully flexed.…”
Section: Stretching Exercisesmentioning
confidence: 99%
See 1 more Smart Citation
“…De modo semelhante, os três estudos encontrados que verificaram o efeito dos exercícios de flexibilidade no desempenho em testes de resistência de força (NELSON et al 2005;FRANCO et al, 2008;GOMES et al, 2010) apresentaram resultados controversos. Nelson et al (2005) encontraram um efeito negativo no desempenho do teste de resistência de força quando precedido de exercícios de flexibilidade estática.…”
unclassified
“…Nelson et al (2005) encontraram um efeito negativo no desempenho do teste de resistência de força quando precedido de exercícios de flexibilidade estática. Já os outros dois estudos não observaram diferenças no resultado do teste de resistência de força quando precedido de exercícios de flexibilidade pelo método estático (FRANCO et al, 2008;GOMES et al, 2010).…”
unclassified